Examining the Reading Performance and Problems among Students in Indonesian Higher Education - Adi Isma; Sahril Nur (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2023)
The objectives of the study are to assess the students' reading performance and explore their problems in comprehending English texts. To achieve these objectives, a descriptive research design was employed. The participants consisted of 76 English Department students from the Faculty of Teachers Training and Education at Universitas Sulawesi Barat, Majene, Indonesia. Two instruments were used in this study. First, a test was administered to measure students' reading performance. Second, a questionnaire in the form of a Google Form was employed to gather students' self-reported responses regarding their problems and difficulties in reading English texts. The findings revealed that the students' mean score on the reading performance test was 47.24, indicating a relatively low reading performance among the students. Moreover, the questionnaire responses indicated that most students reported encountering problems and difficulties in comprehending English reading texts. Consequently, it can be inferred that students' reading performance is adversely affected by these challenges. Based on the results, this study recommends the integration of learning media, technological tools, and effective reading strategies to address the identified problems and improve students' reading skills. These practical recommendations aim to provide educators and researchers with actionable strategies to improve the reading proficiency of EFL students.